The Zika Contraception Access Network: a feasibility programme to increase access to contraception in Puerto Rico during the 2016–17 Zika virus outbreak. (February 2018) - Lathrop, Eva; Romero, Lisa; Hurst, Stacey; Bracero, Nabal; Zapata, Lauren B; Frey, Meghan T; Rivera, Maria I; Berry-Bibee, Erin N; Honein, Margaret A; Monroe, Judith; Jamieson, Denise J
Summary: Background: Prevention of unintended pregnancy is a primary strategy to reduce adverse pregnancy and birth outcomes related to Zika virus infection. The Zika Contraception Access Network (Z-CAN) aimed to build a network of health-care providers offering client-centred contraceptive counselling and the full range of reversible contraception at no cost to women in Puerto Rico who chose to prevent pregnancy during the 2016–17 Zika virus outbreak. Here, we describe the Z-CAN programme design, implementation activities, and baseline characteristics of the first 21 124 participants. Methods: Z-CAN was developed by establishing partnerships between federal agencies, territorial health agencies, private corporations, and domestic philanthropic and non-profit organisations in the continental USA and Puerto Rico. Private donations to the National Foundation for the Centers for Disease Control and Prevention (CDCF) secured a supply of reversible contraceptive methods (including long-acting reversible contraception), made available to non-sterilised women of reproductive age at no cost through provider reimbursements and infrastructure supported by the CDCF. To build capacity in contraception service provision, doctors and clinic staff from all public health regions and nearly all municipalities in Puerto Rico were recruited into the programme. All providers completed 1 day of comprehensive training in contraception knowledge, counselling, and initiation and management, including the insertion and removal of long-acting reversible contraceptives (LARCs). Z-CAN was announced through health-care providers, word of mouth, and a health education campaign. Descriptive characteristics of programme providers and participants were recorded, and we estimated the factors associated with choosing and receiving a LARC method. As part of a Z-CAN programme monitoring plan, participants were invited to complete a patient satisfaction survey about whether they had obtained free, same-day access to their chosen contraceptive method after receiving comprehensive counselling, their perception of the quality of care they had received, and their satisfaction with their chosen method and services. Findings: Between May 4, 2016, and Aug 15, 2017, 153 providers in the Z-CAN programme provided services to 21 124 women. 20 110 (95%) women received same-day provision of a reversible contraceptive method. Whereas only 767 (4%) women had used a LARC method before Z-CAN, 14 259 (68%) chose and received a LARC method at their initial visit. Of the women who received a LARC method, 10 808 (76%) women had used no method or a least effective method of contraception (ie, condoms or withdrawal) before their Z-CAN visit. Of the 3489 women who participated in a patient satisfaction survey, 3068 (93%) of 3294 women were very satisfied with the services received, and 3216 (93%) of 3478 women reported receiving the method that they were most interested in after receiving counselling. 2382 (78%) of 3040 women rated their care as excellent or very good. Interpretation: Z-CAN was designed as a short-term response for rapid implementation of reversible contraceptive services in a complex emergency setting in Puerto Rico and has served more than 21 000 women. This model could be replicated or adapted as part of future emergency preparedness and response efforts. Funding: National Foundation for the Centers for Disease Control and Prevention .